On the characterisation of antisite defects and ordering in off-stoichiometric Fe2VAl-based Heusler compounds by X-ray anomalous diffraction. (1st January 2018) - van der Rest, Camille; Schmitz, Alain; Jacques, Pascal J.
Abstract: Compounds based on Fe2 VAl are good candidates for low grade heat harvesting owing to the thermoelectric effect. However, it is claimed that their thermoelectric properties are badly influenced by antisite defects, especially at higher temperatures. The present study investigates order-disorder transitions in Fe2 VAl ternary Heusler compounds. An inherent problem of these compounds is the close atomic numbers of Fe and V, leading to similar x-ray atomic scattering factors. Hence, the D03 and L21 structures, corresponding to Fe-V antisite defects, are hardly distinguishable by X-ray diffraction. In this work, anomalous scattering and neutron diffraction were successfully combined with differential scanning calorimetry to highlight the order-disorder transitions in Fe2 VAl-based compounds. A model has been developed to quantify the ordering parameters. From these results, specific heat-treatments were defined to promote the formation of the L21 ordered phase. Graphical abstract: Image 1